Twitter Discourse: The Necessary Melding of Ethics and Digital Activism: The Necessary Melding of Ethics and Digital Activism - Isma Adila; Nikita E. Santanasyah; Alanis Desra Marja Arif; Lenia Ajeng Titiasa; Erlangga Firdaus (ULTIMA Comm, 2023)
This paper draws upon how digital activism, by using hashtag (#) is influencing audience discourse on Twitter platform, with particular cases carried out by the twitter account @PartaiSocmed. This twitter account is anonymously focused on creating threads, containing unofficial information, photos, videos of public officials- politicians, related to their wealth and family. In the second section, this paper will also discuss how this social media activism and discourse also has lateral issues related with doxing and privacy breaching. Moreover, this research will mainly be using Sentiment Analysis as tools to reveal how social media has been used, for digital activism and asserting important issues. In addition, the author highlights, there is power in the attention online activism brings, also online activists need to work on a way to improve the quality of the discourse by developing habits and operating under standards to make them more ethical.